PENGARUH PERBANDINGAN MOLAR DAN DURASI REAKSI TERHADAP RENDEMEN BIODIESEL DARI MINYAK KELAPA (Coconut Oil) - Risa Inggit Pramitha; Agus Haryanto; Sugeng Triyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
This study aims to determine the effect of the molar ratio of oil : methanol and duration of the reaction on theyield of biodiesel produced from palm oil transesterification. The transesterification reaction is carried outusing coconut oil at 60 °C and 0.5 grams of NaOH catalyst. The method is a completely randomized design witha combination of two factors, namely the molar ratio and the duration of the reaction. The molar ratio consistsof four levels (1: 3, 1: 4, 1: 5 and 1: 6), while the duration of the reaction is composed of three levels (15, 30, and60 minutes). Parameter observations include yield, density, and viscosity of biodiesel produced. Each unit ofexperiment was performed using 100 ml of coconut oil and each treatment was repeated three times. Theresults showed that duration factor significantly influence the yield and viscosity of biodiesel, while the molarratio factor significantly influence the viscosity of biodiesel. Interaction of these factors, however, do not affectparameters observed. The highest yield of biodiesel (75.56%) resulted within duration of 60 minutes andthe lowest (60.27%) on within duration of 15 minutes. Biodiesel produced has a density of 0.86 to 0.87 g/ml(complies SNI), and a viscosity of between 3.40 to 4.55 cSt